2021
DOI: 10.1021/acs.jpcb.1c06944
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding of Epirubicin Hydrochloride with Single Nucleotide Mismatched DNA and Subsequent Sequestration by a Mixed Micelle

Abstract: Targeting mismatched base pairs containing DNA using small molecules and exploring the underlying mechanism involved during the binding interactions is one of the fundamental aspects of drug design. These molecules in turn are used in nucleic acid targeted therapeutics and cancer diagnosis. In this work, we systematically delineate the binding of the anticancer drug, epirubicin hydrochloride (EPR) with 20-mer duplex DNA, having both natural nucleobase pairing and thermodynamically least stable non-Watson−Crick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…It must be stated here, the probe (here NR) does not show any loss in fluorescence signal during the experiment as evident from Figure S12. Only NR displays a typical single component diffusion with a time constant ∼72 μs as evident from the recorded autocorrelation function trace (Figure 5a), which is well corroborated with a previously reported drug, Epirubicin Hydrochloride, from our group [41] . On the contrary, the longer lag time component of the diffusion arises from the fibrillar binding site as evident from Figure 5a, and Table S5.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…It must be stated here, the probe (here NR) does not show any loss in fluorescence signal during the experiment as evident from Figure S12. Only NR displays a typical single component diffusion with a time constant ∼72 μs as evident from the recorded autocorrelation function trace (Figure 5a), which is well corroborated with a previously reported drug, Epirubicin Hydrochloride, from our group [41] . On the contrary, the longer lag time component of the diffusion arises from the fibrillar binding site as evident from Figure 5a, and Table S5.…”
Section: Resultssupporting
confidence: 89%
“…Only NR displays a typical single component diffusion with a time constant ~72 μs as evident from the recorded autocorrelation function trace (Figure 5a), which is well corroborated with a previously reported drug, Epirubicin Hydrochloride, from our group. [41] On the contrary, the longer lag time component of the diffusion arises from the fibrillar binding site as evident from Figure 5a, and Table S5. From Figure 5a, Table 1, and Table S5, it is observed that the longer lag-time component and corresponding relative amplitude increases which attributes the binding of NR to Trypsin Fib.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations